Comprehensive toxicokinetic analysis reveals major interspecies differences in absorption, distribution and elimination of citrinin in pigs and broiler chickens. (July 2020) - Meerpoel, Celine; Vidal, Arnau; Huybrechts, Bart; Tangni, Emmanuel K.; De Saeger, Sarah; Croubels, Siska; Devreese, Mathias
Abstract: A comprehensive toxicokinetic analysis of citrinin (CIT) revealed interspecies differences for all toxicokinetic parameters and in absolute oral bioavailability. Oral bioavailability for CIT was complete for broilers (113–131%), while ranging from 37 to 44% in pigs. CIT was more rapidly absorbed in pigs (Tmax  = 0.92 h) compared to broiler chickens (Tmax  = 7.33 h). The elimination of CIT was slower in pigs (T1/2el  = 26.81 h after intravenous (IV) administration) compared to chickens (T1/2el  = 1.97 h after IV administration), due to the striking difference in clearance (Cliv= 9.87 mL/h/kg for pigs versus Cliv  = 863.09 mL/h/kg for broilers). Also, the volume of distribution differed significantly between pigs (Vd = 0.30 L/kg after IV administration) and chickens (Vd = 2.46 L/kg after IV administration). However, plasma protein binding did not differ statistically significant (91–98%). It is imperative to further investigate biotransformation and elimination pathways in different species, including humans. Highlights: Toxicokinetic characteristics of citrinin showed species dependency. Citrinin was completely absorbed in broiler chickens, but incomplete in pigs. The elimination half-life for citrinin was lower for broilers compared to pigs. Similarities and differences in toxicokinetics of ochratoxin A were described.